Mesial temporal lobe epilepsy with hippocampal sclerosis is infrequently associated with neuronal autoantibodies. (26th August 2018) - Nóbrega‐Jr, Adaucto W.; Gregory, Christian P.; Schlindwein‐Zanini, Rachel; Neves, Fabricio de Souza; Wolf, Peter; Walz, Roger; Steindel, Mario; Lin, Katia
Summary: Mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE‐HS) is characterized by its well‐defined clinical profile. Limbic encephalitis is increasingly recognized as a possible etiology of adult‐onset MTLE‐HS, and neuronal autoantibodies have been detected in patients even without previous signs of encephalitis. The aim of this study is to analyze the frequency of specific autoantibodies in patients with MTLE‐HS. A case‐control study was carried out with 100 patients with MTLE‐HS and 50 healthy controls. Sera samples from subjects were tested by indirect immunofluorescence assay for detection of anti‐ N ‐methyl‐d ‐aspartate receptor (NMDA‐R), anti‐contactin‐associated protein‐like 2 (CASPR2), anti‐leucine‐rich glioma inactivated 1 (LGI1), anti‐gamma aminobutyric acid B receptor (GABA‐B‐R), anti‐alpha‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid 1 and 2 receptors (AMPA‐1‐R and AMPA‐2‐R), and enzyme‐linked immunosorbent assay for detection of anti‐glutamic acid decarboxylase 65 (GAD65). Mean age of patients and controls was 41.2 vs 42 years, and 55% vs 56% were female. Mean duration of epilepsy was 27.2 years. No neuronal autoantibodies were found in either group, except for anti‐GAD65 in 3 patients and 2 controls. This study adds to the mounting evidence that, in Brazilian patients, MTLE‐HS without signs and symptoms of autoimmune encephalitis may be infrequently associated with these autoantibodies. Differences regarding accuracy of used methodologies for autoantibody detection and genetic and environmental characteristics are discussed. Further works with different methodologies tested simultaneously in different populations may help clarify the incongruent study results about autoantibodies in MTLE‐HS.